Motivation in the 21st Century: Why do teachers stay in the profession? - Mills, Shannon (2017)
This study explores the different motivating factors experienced by teachers, both Primary and Secondary, in the 21st Century. It is a study set against a backdrop of both large scale educational reform, not seen since the introduction of the first National Curriculum in 1988, and a teacher recruitment and retention crisis. The research conducted here aims to discover the real reasons behind why teachers remain in the profession despite these issues and has hence been conducted using a predominantly qualitative paradigm. Four schools were approached regarding their participation in the study and three of these consented to become part of the study. From across these three schools 31 out 45 teachers completed and returned the questionnaires they were asked to answer. Two follow up interviews were also conducted using a semi-structured interview technique; although both of the teachers interviewed were Secondary school teachers they had entered the profession through different methods and had different levels of experience within teaching. An analysis of the results revealed that the teachers surveyed maintain their motivation primarily due to a mixture of both intrinsic and extrinsic factors. Although the number of extrinsic factors outweighed intrinsic ones, it is clear that the most important motivating factors for teachers appeared to be intrinsic.